The influence of water table depth on evapotranspiration in the Amazon arc of deforestation - J. O'Connor; M. J. Santos; K. T. Rebel; S. C. Dekker; S. C. Dekker (Hydrology and Earth System Sciences, 2019)
The Amazon rainforest evapotranspiration (ET) flux provides climate-regulating and moisture-provisioning ecosystem services through a moisture recycling system. The dense complex canopy and deep root system creates an optimum structure to provide large ET fluxes to the atmosphere, forming the source of precipitation. Extensive land use and land cover change (LULCC) from forest to agriculture in the arc of deforestation breaks this moisture recycling system. Crops such as soybean are planted in large homogeneous monocultures and the maximum rooting depth of these crops is far shallower than forest. This difference in rooting depth is key as forests can access deep soil moisture and show no signs of water stress during the dry season, while in contrast crops are highly seasonal with a growing season dependent on rainfall. As access to soil moisture is a limiting factor in vegetation growth, we hypothesised that if crops could access soil moisture, they would undergo less water stress and therefore would have higher evapotranspiration rates than crops which could not access soil moisture. We combined remote-sensing data with modelled groundwater table depth (WTD) to assess whether vegetation in areas with a shallow WTD had higher ET than vegetation in deep WTD areas. We randomly selected areas of forest, savanna, and crop with deep and shallow WTD and examined whether they differ on MODIS Evapotranspiration (ET), Land Surface Temperature (LST), and Enhanced Vegetation Index (EVI), from 2001 to 2012, annually and during transition periods between the wet and dry seasons. As expected, we found no differences in ET, LST, and EVI for forest vegetation between deep and shallow WTD, which because of their deep roots could access water and maintain evapotranspiration for moisture recycling during the entire year. We found significantly higher ET and lower LST in shallow WTD crop areas than in deep WTD during the dry season transition, suggesting that crops in deep WTD undergo higher water stress than crops in shallow WTD areas. The differences found between crop in deep and shallow WTD, however, are of low significance with regards to the moisture recycling system, as the difference resulting from conversion of forest to crop has an overwhelming influence (ET in forest is ≈2 mm d−1 higher than that in crops) and has the strongest impact on energy balance and ET. However, access to water during the transition between wet and dry seasons may positively influence growing season length in crop areas.